Four-Dimensional Flow MRI Quantification of Blood Flow in Bicuspid Aortic Valve - Gordon, Daniel Z. (J Thorac Imaging, 2020)
BACKGROUND: Four-Dimensional (4D) flow MRI is limited by time-consuming and non-standardized data analysis. We aimed to test the efficiency and inter-observer reproducibility of a dedicated 4D flow MRI analysis workflow. METHODS: Thirty retrospectively identified patients with bicuspid aortic valve (BAV, age=47.8±11.8years, 9 male) and 30 healthy controls (age=48.8±12.5years, 21 male) underwent Aortic 4D flow MRI using 1.5&3T MRI systems (Siemens, Germany). Two independent readers performed 4D flow analysis on a dedicated workstation (Circle; Calgary, Canada) including pre-processing, aorta segmentation, and placement of four 2D planes throughout the aorta for quantification of net flow, peak velocity, and regurgitant fraction. 3D flow visualization using streamlines was used to grade aortic valve outflow jets and extent of helical flow. RESULTS: 4D flow analysis workflow time for both observers: 5.0±1.4 minutes per case (range 3–10 minutes). Valve outflow jets and flow derangement was visible in all 30 BAV patients (both observers). Net flow, peak velocity, and regurgitant fraction was significantly elevated in BAV patients compared to controls except for regurgitant fraction in plane 4 (91.1±29.7ml/s versus 62.6±19.6ml/s, 37.1% difference; 121.7±49.7cm/s versus 90.9±26.4cm/s, 28.9% difference; 9.3±10.1% versus 2.0±3.4%, 128.0% difference, respectively; p<0.001). Excellent ICC agreement for net flow: 0.979, peak velocity: 0.931 and regurgitant fraction: 0.928. CONCLUSION: Our study demonstrates the potential of an efficient data analysis workflow to perform standardized 4D flow MRI processing in under 10 minutes and with good-to-excellent reproducibility for flow and velocity quantification in the thoracic aorta.